Connecting worlds: indigenous territories, habitat suitability and conservation of the three large carnivores (Mammalia: Carnivora) of Oaxaca, Mexico - Guerrero-Montes de Oca, Emilia; Gómez Hoyos, Camilo; Mejía Franco, Fabián; Botello López, Francisco Javier; Sánchez-Cordero, Víctor; Arias-Alzate, Andrés (Ethnobiology and Conservation, 2021)
Human and wildlife conflicts pose conservation challenges for several charismatic species worldwide. Given their close long-standing interactions with wildlife, indigenous communities set an interesting framework to identify factors establishing these relationships. The first step is to account the perceptions and symbolisms of indigenous communities to define and complement conservation efforts. We used multi-temporal and multi-criteria analyses to assess species habitat suitability of three large carnivores (jaguar, puma, and coyote), and quantified the overlap with the Mixtec and Zapotec indigenous territories in southern Mexico. We observed a positive and proactive relationship between indigenous communities’ self-identification and a high species habitat suitability for the conservation of these large carnivores in the Sierra Norte, Sierra Sur, Coastal, and Mixtec regions. Given that most of these areas occur outside natural protected areas, the inclusion of indigenous communities in the management and planning of their territory is crucial for preserving their ethnocentric vision and ensuring long-term conservation of these charismatic large carnivores and their habitat.